A RATIONAL SOLUTION FOR THE ECONOMICAL HOUSING LAYOUTS - Rasul-Zade Lobar; Khamrakulova М. А; Jabborov Abdulaziz (International Engineering Journal For Research & Development, 2021)
The article discusses the affordable housing creating issues for a wide citizens category. The most important factor determining the ability to purchase your own home is its cost. And one of the ways to reduce it is the block-type residential buildings construction balanced in space-planning decisions.